1998
DOI: 10.1002/hep.510280432
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus replication in human HepG2 cells mediated by hepatitis B virus recombinant baculovirus

Abstract: Hepatitis B virus (HBV) is a small, double-stranded DNA virus and is the prototype of the hepadnavirus family. HBV is a human pathogen capable of causing both acute and chronic hepatitis. The World Health Organization currently estimates that 350 million people are chronically infected with HBV. Persistent HBV infection is also associated with an increased risk of cirrhosis and hepatocellular carcinoma. 1 Although a tremendous amount is known about HBV, our knowledge of the virus is by no means complete. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 52 publications
9
153
1
Order By: Relevance
“…Baculovirus stocks and titers were prepared in Sf21 insect cells as described in Delaney and Isom. 69 Baculovirus was diluted in DMEM/F12 (control medium), calcium-free DMEM, or calcium-free DMEM medium supplemented with a designated concentration of EGTA to a final volume of 0.5 ml. Incubation of cultures with baculovirus for less than 40 min resulted in decreased gene transfer efficiencies, whereas no difference was observed if cultures were incubated for X1 h (data not shown).…”
Section: Infection Of Primary Rat Hepatocytes With Recombinant Cmv-lamentioning
confidence: 99%
“…Baculovirus stocks and titers were prepared in Sf21 insect cells as described in Delaney and Isom. 69 Baculovirus was diluted in DMEM/F12 (control medium), calcium-free DMEM, or calcium-free DMEM medium supplemented with a designated concentration of EGTA to a final volume of 0.5 ml. Incubation of cultures with baculovirus for less than 40 min resulted in decreased gene transfer efficiencies, whereas no difference was observed if cultures were incubated for X1 h (data not shown).…”
Section: Infection Of Primary Rat Hepatocytes With Recombinant Cmv-lamentioning
confidence: 99%
“…To test the effectiveness of sRz in cell culture, HepG2 cells were maintained in minimal essential medium supplemented with 10% heat-inactivated fetal bovine serum in a humidified incubator at 37 8C with 5% CO 2 + These cells were cotransfected with pBB4+5HBV1+3 (a 1+3ϫ unit length HBV DNA plasmid construct; see Delaney & Isom, 1998) and either pLSCLIP, pLSCLIPmRz408, pLSCLIPsRz777, or pLSCLIPsRz885 (pLSCLIP denotes the CLIP cassette in the LacSwitch vector, from Stratagene)+ pLSCLIPsRz777 and pLSCLIPsRz885 were constructed by annealing reverse complementary oligonucleotides (CLAW437/CLAW438 and CLAW397/CLAW398, respectively) and then inserting them into the Bgl II site of pLSCLIP+ pLSCIPmRz408 was constructed the same way with oligonucleotides CLAW435/ CLAW436+ However, these oligonucleotides were inadvertently synthesized so that the 59 flanking region contained mismatches; subsequent testing in vitro showed that this ribozymes had approximately 15% of the catalytic activity of the sRz408, which was equivalent to the activity of mRz247, and it was therefore included in the experiments as a "intermediateactivity" comparison+ Finally, we also employed the mRz CLIP that had been constructed previously (using the same procedures)+ HepG2 cells were transfected using FuGENE6 transfection reagent (Boehringer Mannheim)+ A total of 5 mg of DNA (0+5 mg pBB4+5HBV1+3 and 4+5 mg of the pLSCLIP constructs) in 10 mL FuGENE6 was used to transfect a 60-mm dish of cells seeded 24 h prior to transfection+ The reagent/ DNA mixture was incubated in serum-containing medium for 24 h+ All transfections were done independently in triplicate+ Control transfections using b-galactosidase showed a transfection efficiency of approximately 30%+…”
Section: Effects Of Ribozymes On Hbv Replication In Cell Culturementioning
confidence: 99%
“…This amino acid exchange in the polymerase sequence (YMDD to YPDD) also resulted in an exchange in the surface protein (IWMM to IRMM). The previously described procedure for baculovirus transduction of HepG2 (Delaney & Isom, 1998) was modified slightly. Briefly, HepG2 cells were transduced at 80 % confluency (1610 5 -2610 5 cells cm 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility that can be used to trigger intracellular HBV replication is to use systems based on the transduction of HepG2 cells with recombinant adenovirus or baculovirus carrying the HBV genome (Delaney & Isom, 1998;Ren & Nassal, 2001). Transduction of hepatoma cells with HBV-loaded baculovirus has led to higher HBV replication levels compared with both transfection approaches and stable cell lines such as HepG2.2.15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation